Phase compensation in single echo acquisition imaging. - McDougal, M.P (IEEE Engineering in medicine and biology magazine)
Parallel imaging in magnetic resonance imaging is currently the primary route to decreasing scan time. Single echo acquisition (SEA) imaging is a completely parallel imaging method that collects a full image in a single echo. This article discusses the implications related to imaging with voxel-sized coils, specifically as they relate to the potential for SEA imaging with large planar and cylindrical arrays. Phased array coils with large numbers of elements have been used to form images in SEA imaging. As implemented, the array elements are on the order of the voxel dimensions in one direction. A complication that arises in this case is the potential for signal loss due to the phase variation over the voxel impressed by the receive coil. This problem has been investigated for the cases of planar and cylindrical arrays. In the case of planar arrays, a single phase compensation pulse can be shown to easily eliminate the dephasing of the radio frequency (RF) coil. Unfortunately, for cylindrical arrays, the rotation of the coil phase gradient requires different phase compensation gradient strengths to optimize the signal from each coil, an obvious problem in single echo imaging. One potential solution is to use the cylindrical coil in the transmit/receive mode, which eliminates the need for phase compensation entirely but will require a more complex interface to the scanner.